(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Logical thinking is a core cognitive competence that supports children’s later success in school learning, problem solving, and everyday decision-making. In preschool age, logical thinking develops most naturally when children work with meaningful, hands-on tasks that require comparison, classification, sequencing, pattern recognition, and simple reasoning. Elementary mathematics activities are especially effective for this purpose because they combine concrete materials, language, symbols, and rules in ways young children can explore actively. This article discusses how thoughtfully designed early mathematics experiences—counting and subitizing, sorting and classifying, building patterns, measuring and comparing, working with shapes and spatial relations, and solving age-appropriate “story problems”—can strengthen preschool children’s logical thinking.